Cohort multiple randomized controlled trial in pediatric asthma to assess the long- and short-term effects of eHealth interventions: protocol of the CIRCUS study - Tamara Ruuls; Romi Sprengers; Vera Hengeveld; Boony Thio; Monique Tabak; Deborah Zagers; Job van der Palen; Mattiènne van der Kamp (Therapeutic Advances in Respiratory Disease)
Background: Asthma is one of childhood’s most prevalent chronic conditions significantly impacting the quality of life. Current asthma management lacks real-time, objective, and longitudinal monitoring reflected by a high prevalence of uncontrolled asthma. Long-term home monitoring promises to establish new clinical endpoints for timely anticipation. In addition, integrating eHealth interventions holds promise for timely and appropriate medical anticipation for controlling symptoms and preventing asthma exacerbations. Objectives: This study aims to provide a pragmatic study design for gaining insight into longitudinal monitoring, assessing, and comparing eHealth interventions’ short- and long-term effects on improving pediatric asthma care. Design: The CIRCUS study design is a cohort multiple randomized controlled trial (cmRCT) with a dynamic cohort of 300 pediatric asthma patients. Methods: The study gathers observational and patient-reported measurements at set moments including patient characteristics, healthcare utilization, and asthma, clinical, and environmental outcomes. Participants are randomly appointed to the intervention or control group. The effects of the eHealth interventions are assessed and compared to the control group, deploying the CIRCUS outcomes. The participants continue in the CIRCUS cohort after completing the intervention and its follow-up. Results: This study was ethically approved by the Medical Research Ethics Committee (NL85668.100.23) on February 15th, 2024. Discussion: The CIRCUS study can provide a rich and unique dataset that can improve insight into risk factors of asthma exacerbations and yield new clinical endpoints. Furthermore, the effects of eHealth interventions can be assessed and compared with each other both short- and long-term. In addition, patient groups within the patient population can be discerned to tailor eHealth interventions to personalized needs on improving asthma management. Conclusion: In conclusion, CIRCUS can provide valuable clinical data to discern risk factors for asthma exacerbations, identify and compare effective scalable eHealth solutions, and improve pediatric asthma care. Trial registration : The protocol is registered at ClinicalTrials.gov (NCT06278662).